Optical solitons for the fractional (3+1)-dimensional NLSE with power law nonlinearities by using conformable derivatives - Korpinar, Z.; İnç, Mustafa; Almohsen, B.; Bayram, M. (Indian Assoc Cultivation Science, 2021)
In this paper, the process of the extended direct algebraic method (EDAM) is used to obtain the optical solitons in fractional (3 + 1)-dimensional nonlinear Schrodinger equation through the conformable derivative. Firstly, this fractional equation is changed into the ordinary differential equation by using the wave variables transformation. Then, new several forms of optical solitons are obtained by using EDAM.
Keywords: Optical solitons; Nonlinear Schrodinger equation; Conformable derivative; Power law nonlinearities; The extended direct algebraic method